Dietary bile acid supplementation alters plasma biochemical and hormone indicators, intestinal digestive capacity, and microbiota of piglets with normal birth weight and intrauterine growth retardation - Liu, Yang; Azad, Md. Abul Kalam; Zhu, Qian; Yu, Zugong; Kong, Xiangfeng (Frontiers in Microbiology, 2022)
Piglets with intrauterine growth retardation (IUGR) have poor small intestinal morphology and function, resulting in impaired digestion and absorption of nutrients and lower growth performance. Bile acids (BA) are important in regulating digestive enzyme activity, digestion and absorption of lipids, intestinal development, and protecting the liver. The present study aimed to investigate the effects of dietary BA on plasma biochemical and hormone indicators, intestinal morphology and function, and microbial community in piglets with normal birth weight (NBW) and IUGR. Weaned piglets (24 IUGR and 24 NBW) were allocated to four groups (12 piglets per group) and fed the following diets: (i) NBW group, NBW piglets fed a basal diet; (ii) NBW  BA group, NBW piglets fed a basal diet with 400 mg/kg BA; (iii) IUGR group, IUGR piglets fed a basal diet; and (iv) IUGR  BA group, IUGR piglets fed a basal diet with 400 mg/kg BA. The feeding trial lasted 28 days. The results showed that IUGR decreased the weight and length of the jejunum, ileum index, and pancreas weight, whereas dietary BA decreased the jejunum weight, the length, weight, and index of ileum in NBW piglets (P < 0.05). Furthermore, IUGR increased (P < 0.05) the plasma choline esterase and glucose levels of weaned piglets regardless of BA supplementation. Dietary BA increased the albumin, triglyceride, and total protein concentrations while decreased plasma aspartate transaminase (AST), alanine aminotransferase (ALT), CHE, lactate dehydrogenase, and NH3 levels regardless of IUGR (P < 0.05). The IUGR increased trypsin level in the ileum, whereas dietary BA decreased jejunal trypsin and lipase and ileal lipase levels of weaned piglets regardless of IUGR (P < 0.05). Spearman’s correlation analysis revealed the potential link between the intestinal microbial community and intestinal health-related indices of weaned piglets. These findings suggest that IUGR could decrease small intestinal morphology and function, whereas dietary BA could promote the ileum development of NBW piglets, protect the liver by reducing plasma ALT and AST levels, and increase the proportion of potentially beneficial bacteria in small intestine of NBW and IUGR piglets, contributing to intestinal development and health of weaned piglets.